Review of the genus Kerzhnerocossus Yakovlev, 2011 (Lepidoptera: Cossidae) with descriptions of two new species from Russia and Mongolia - Saldaitis, Aidas; Yakovlev, Roman V.; Truuverk, Andro (Zootaxa, 2017)
Two new species of Kerzhnerocossus (Lepidoptera, Cossidae) are described: K. tannuolus sp. nov. from Russia: Tuva, and K. kamelini sp. nov. from Mongolia. The genus now comprises three species.